Karmayogi : a biography of E. Sreedharan - Ashokan,M. S; Rajamohan, Rajesh (New Delhi : Penguin, 2015)
Biography of E. Sreedharan, born 1932, railroad engineer and former director of Delhi Metro Rail Corporation, India.